Financial sustainability and capital leverage of microfinance institutions in China: The mediating role of profitability - Yue Li; Zariyawati Mohd Ashhari; Yaojun Fan (Cogent Economics & Finance, 2022)
This study primarily investigates the effect of financial sustainability on capital leverage in microfinance setting. In doing this, this study looks at operating performance of 45 commercial microfinance institutions under current dual pressure of downturn and deleveraging in China. Empirically, this study employs the system GMM to observe a robustly small and negative impact of financial sustainability on capital leverage. Furthermore, this study presents a conclusion with evidence by mediation analysis that profitability exhibits a suppressing effect on the relationship between financial sustainability and capital leverage. Theoretically, this study verifies that the impact of financial sustainability on capital structure obeys the pecking order theory.
Keywords: 330; capital leverage; Financial sustainability; microfinance institutions; profitability